Deleuze and the physically active body - Markula, Pirkko 1961- (Routledge research in sport, culture and society, 2019)
This volume examines Gilles Deleuze's philosophy as it relates to the study of the physically active body. It explores theoretical and practical examples of how the physically active body can be examined as a material, social, political, and cultural entity using a Deleuzian perspective. Examining topics such as, the formation of thought within a capitalist system; sport, exercise, and dance as cultural arrangements; researching the physically active body from a Deleuzian perspective; and Deleuze on Foucault, this book shows ways of investigating the moving body as an agent for initiating social change. This is fascinating reading for students and researchers working in the fields of the Sociology of Sport, Sport and Politics, and Sport and Social Theory